The use of EPIC model to study the agroecological change during 93 years of farming transformation in the Argentine pampas - Bernardos, Jaime Nicolas (2001)
A non-conventional use of the EPIC simulation model is proposed to analyse and interpret changes in agroecological functions during a 93-year farming period in the Argentine pampas. The simulation was divided in seven different time periods in order to process data representing significant combinations of weather (rainfall and winds), land use (land allocated to crops and pastures), and technology (agronomic practices and farming inputs) conditions. EPIC parameters were modified according to those conditions for calibration. Model validation involved the replication of relevant past ecological and agricultural events recorded in historical documents, or quantified in regional statistics, field measurements, and experimental data sets. EPIC seems to be useful tool for (1) making sound ecological interpretation and inference, and (2) testing applications of ecological principles in farming.